2017
DOI: 10.1177/2050312117722569
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and transcriptomic analyses to explain the pleiotropic effects of Ankaferd blood stopper

Abstract: Ankaferd blood stopper is a standardized mixture of the plants Thymus vulgaris, Glycyrrhiza glabra, Vitis vinifera, Alpinia officinarum, and Urtica dioica and has been used as a topical hemostatic agent and with its clinical application established in randomized controlled trials and case reports. Ankaferd has been successfully used in gastrointestinal endobronchial mucosal and cutaneous bleedings and also in abdominal, thoracic, dental and oropharyngeal, and pelvic surgeries. Ankaferd’s hemostatic action is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…9,17-19 Dynactin, Egr-1, Midkine, NF-1, Twinfilin, V-myc, and Yin Yang 1 can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms. 15 This study demonstrated that IL-1β expressions are significantly down-regulated in the ABS group compared with the other two groups. Although our study is the first to investigate the expression of IL-1β in ABS treated cervical mucosa, a study by Amanvermez et al 20 IL-1β and Interleukin-10 (IL-10) investigated expressions during the fracture healing process with or without ABS application to the bone fracture.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…9,17-19 Dynactin, Egr-1, Midkine, NF-1, Twinfilin, V-myc, and Yin Yang 1 can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms. 15 This study demonstrated that IL-1β expressions are significantly down-regulated in the ABS group compared with the other two groups. Although our study is the first to investigate the expression of IL-1β in ABS treated cervical mucosa, a study by Amanvermez et al 20 IL-1β and Interleukin-10 (IL-10) investigated expressions during the fracture healing process with or without ABS application to the bone fracture.…”
Section: Discussionmentioning
confidence: 62%
“…ABS is a novel hemostatic agent that has pleiotropic and profound effects on the hematologic and immune system including anti-microbial, anti-neoplastic, anti-mutagenic, and antioxidant as well as tissue-healing properties. 6,15,16 The mechanistic basis of this pleiotropism remains a mystery despite extensive research during the past decade. It has been suggested that the unique action of the ABS mechanism mainly depends on the protein agglutination and polymerization that modulates the erythroid aggregation and vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathophysiology underlying the unique effect of ABS remains an area of active investigation, the anti-inflammatory effect of ABS is reported to be based on the effect of proinflammatory cytokines including IL-6, IL-1β and TNF-α. Moreover, Dynactin, EGR-1, Midkine, NF-1, Twinfilin, V-Myc, and YY1 (Yin Yang 1) can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms [46] . Studies also highlight the potential benefits of ABS in numerous distinct inflammatory conditions related to the oral mucosa, intestinal mucosa, cartilage tissue, liver, pericardium, cervix and uterus [19] , [47] , [48] , [49] , [50] , [51] .…”
Section: Evaluation and Discussion Of The Hypothesismentioning
confidence: 99%
“…It has many proven effects on the hemostatic and immune system. In addition to antimicrobial, antineoplastic, antimutagenic, and antioxidant effects, it is also effective in wound healing (5,15,16) .The anti-inflammatory effect of ABS was shown in studies on cartilage tissue, gastric mucosa, pericardial tissue, and the liver (17,18,19,20) . A study on a caustic esophageal injury model, which demonstrated improved inflammation in the esophagus and reduced stricture formation, led to the consideration that the anti-inflammatory effects of ABS may be beneficial for the adhesions in the endometrium (8) .…”
Section: Discussionmentioning
confidence: 99%